Homicide a forensic psychology casebook - Swart, Joan; Mellor, Lee (CRC Press, Taylor & Francis Group, 2017)
This book guides readers through the practical aspects of homicide cases across the entire criminal justice system, from the investigative process to the criminal trial process, and beyond. Criminal justice students and practitioners alike will benefit from the comprehensive scope of this text.